Financial Liberalization and Current Account Balance - Radoslaw SLUSARCZYK (Communications of International Proceedings, 2025)
The article analyzes the relationship between financial liberalization and the current account balance. It thus attempts to answer the question of how financial market deregulation affects international trade. There are two main arguments in favor of undertaking this research topic. The first concerns the search for answers to the question of the consequences of financial market deregulation for the real economy. The second concerns the identification of the determinants of permanent trade deficits. The impact of financial liberalization on a nation’s external balance is a crucial consideration, particularly given recent shifts in global trade policy. The article presents the theoretical channels through which financial liberalization affects trade. The empirical analysis covered 35 countries from 1973 to 2019, primarily OECD countries. As part of the research process, a financial liberalization index covering a wide range of instruments regulating its functioning was used to measure the phenomenon of financial liberalization. The study used comparative analysis and Granger causality analysis (Granger Dumitrescu-Hurlina causality test). An analysis of deregulation episodes in the studied countries revealed that financial liberalization was, on average, followed by an improvement in the current account balance. These findings were corroborated across various time intervals during the period of financial sector reform. Additionally, the research confirmed the presence of Granger causality between the level of financial liberalization and the current account balance. Utilizing the Granger-Dumitrescu-Hurlin causality test, it was demonstrated that financial liberalization serves as a Granger cause for the current account balance. This relationship holds true regardless of the lag order applied in the analysis. Based on the analysis results, it can be concluded that financial liberalization may have a positive impact on the current account balance.
Keywords: financial liberalization; current account balance; trade deficit; financial repression